MHM: A Multiple Handshaking MAC Protocol for Underwater Acoustic Sensor Networks - Wen Lin; Keyu Chen (International Journal of Distributed Sensor Networks)
Underwater acoustic sensor networks (UWASNs) are effective tools for exploring and observing the ocean. Due to the nonnegligible physical restrictions of the underwater acoustic communication, most MAC protocols applied in the existing terrestrial wireless networks become inapplicable. In this paper, we propose a multiple handshaking MAC protocol for UWASNs called multihandshaking MAC (MHM). Using the method of multiple handshaking and competitive mechanism of control packets, our protocol is proposed to make the contending nodes share the underwater acoustic channel much more fairly and more efficiently. The main idea of MHM is to allow multiple nodes to transmit and receive data packets at the same time without packet collisions. We also propose a competitive mechanism of control packets, which can guarantee that there will not be data collisions in the process of multiple packet transmissions. Simulation results show that our protocol can achieve better performance, including throughput, delay, and fairness.